2016
DOI: 10.1371/journal.pone.0147326
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Assays and Cytology in Primary Cervical Screening of Women Aged 30 Years and Above

Abstract: In women aged ≥30 years, Human Papillomavirus testing will replace cytology for primary cervical screening. We compared Hybrid Capture 2 (HC2), cobas, CLART, and APTIMA HPV assays with cytology on 2869 SurePath samples from women undergoing routine screening at 30–65 years in Copenhagen, Denmark. Women with cytological abnormalities were managed according to routine recommendations, with 92% completeness. Those with cytology-normal/HPV-positive samples (on any of the four assays) were invited for repeated cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 32 publications
(44 reference statements)
6
59
0
Order By: Relevance
“…In addition, no women with benign biopsies had positive HPV 16/18 on Aptima genotyping and no high-grade squamous intraepithelial lesions or worse on biopsy were detected in women with negative HPV 16/18 on Aptima genotyping, which offered superior sensitivity and specificity for high-grade squamous intraepithelial lesions or worse. The findings were consistent with previous studies performed in both screening21 and referral populations 22 23…”
Section: Discussionsupporting
confidence: 93%
“…In addition, no women with benign biopsies had positive HPV 16/18 on Aptima genotyping and no high-grade squamous intraepithelial lesions or worse on biopsy were detected in women with negative HPV 16/18 on Aptima genotyping, which offered superior sensitivity and specificity for high-grade squamous intraepithelial lesions or worse. The findings were consistent with previous studies performed in both screening21 and referral populations 22 23…”
Section: Discussionsupporting
confidence: 93%
“…Although the follow-up with repeated testing was incomplete, it was very similar to that observed in the randomized controlled trials comparing HPV-based to cytology-based primary cervical screening (14). Nevertheless, a somewhat higher number of high-grade CIN would plausibly be detected with a more complete follow-up (6). …”
Section: Discussionmentioning
confidence: 99%
“…The study design was described in detail previously (511). In short, consecutive routine SurePath samples from 5,034 women arriving at the Department of Pathology of Copenhagen University Hospital Hvidovre in June to August 2011 were collected and tested with liquid-based cytology (LBC; reported using the Bethesda 2001 system) and the four HPV assays (this constituted the baseline testing).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ATHENA trial, when excluding patients <30 years, overall hrHPV prevalence found was 8.4% (10.5% including women 25–29 years) [12]. In women from the Danish cervical cancer screening program, the hrHPV prevalence was even higher: 9.4% for Aptima, 11.7% for HC2 and 16.2% for cobas [18]. As earlier described, the hrHPV prevalences found in our study with the 3 different testing solutions were in the same range, although the hrHPV prevalence found by the Aptima assay was found to differ significantly when compared to HC2 (7.5% vs 8.5%, respectively; p-value 0.007).…”
Section: Discussionmentioning
confidence: 99%